Rumours, Bargains and Lies: How to advocate Open Access repositories more successfully - Johnson, Gareth J (2006)
In this workshop seminar delivered twice at the CoFHE/UCR 2006 conference the author explored aspects relating to successful advocacy of Open Access and repositories. Areas covered included preconceptions on the part of academics and support staff, as well as models of implementation of an advocacy programme. A large portion of the material pulls together experience and narrative evidence from the SHERPA Consortium partners and repository administrators; with a particular focus on their successes and failures and the lessons that have been learned.